Components present in the frying oil used and determinants previous to its conversion into biodiesel - Sanaguano Salguero, Herminia (2019)
The residual oils represent a problem for the environment, because they contaminate the water producing an uptake of oxygen that prevents the subsistence of aquatic organisms. This investigation had the objective of determining the components present in the frying oil used from restaurants in the city of Guaranda, Bolívar - Ecuador prior to its conversion to Biodiesel. Samples were obtained from three fast food restaurants the most popular in the city in mention. Physicochemical analyzes were carried out with a filtration starting point, the analyzes performed on the oils were density, acidity, humidity or loss due to heating and refractive index, and their comparison with normative parameters. After the density analysis of the three sample types, an average between 0,918 and 0,920 gr / mL was obtained. In acidity, values between 3,006% and 3,293% were obtained. The humidity values ​​were of an average of 0,099%. In the refractive index, the mean value was 1,459. These values, move away from the regulations for a pure oil so that it can continue to be used as food, however, these waste oils with the characteristics they presented, have been used for conversion into biodiesel.